ZnO nanoparticles efficiently enhance drought tolerance in Dracocephalum kotschyi through altering physiological, biochemical and elemental contents - Karimian, Zahra; Samiei, Leila (Frontiers in Plant Science, 2023)
Using nanofertilizers in certain concentrations can be a novel method to alleviate drought stress effects in plants as a global climate problem. We aimed to determine the impacts of zinc nanoparticles (ZnO-N) and zinc sulfate (ZnSO4) fertilizers on the improvement of drought tolerance in Dracocephalum kotschyi as a medicinal-ornamental plant. Plants were treated with three doses of ZnO-N and ZnSO4 (0, 10, and 20 mg/l) under two levels of drought stress (50% and 100% field capacity (FC)). Relative water content (RWC), electrolyte conductivity (EC), chlorophyll, sugar, proline, protein, superoxide dismutase (SOD), polyphenol oxidase (PPO) and, guaiacol peroxidase (GPO) were measured. Moreover, the concentration of some elements interacting with Zn was reported using the SEM-EDX method. Results indicated that foliar fertilization of D. kotschyi under drought stress with ZnO-N decreased EC, while ZnSO4 application was less effective. Moreover, sugar and proline content as well as activity of SOD and GPO (and to some extent PPO) in treated plants by 50% FC, increased under the influence of ZnO-N. ZnSO4 application could increase chlorophyll and protein content and PPO activity in this plant under drought stress. Based on the results, ZnO-N and then ZnSO4 improved the drought tolerance of D. kotschyi through their positive effects on physiological and biochemical attributes changing the concentration of Zn, P, Cu, and Fe. Accordingly, due to the increased sugar and proline content and also antioxidant enzyme activity (SOD, GPO, and to some extent PPO) on enhancing drought tolerance in this plant, ZnO-N fertilization is advisable.